HUBUNGAN PEMAHAMAN PESAN KEHAMILAN DAN KEPATUHAN KUNJUNGAN ANTENATAL DENGAN KEPATUHAN KONSUMSI TABLET TAMBAH PADA IBU HAMIL TRIMESTER III DI WILAYAH PUSKESMAS TLOGOSARI - Maula, Hikmatul; Trilianto, Arif Eko; Shidiq, Pasidi (Jurnal Keperawatan Profesional, 2021)
One of the health servicestrategies to improve the understanding of pregnant women is the maternal and Child Health (MCH) book. The MCH Handbook is communication tool that contains message on maternal and child health. The massagein the KIA book includes massage for the period of pregnancy that are things that need to be done by pregnant women as wellas the addition of body suplements suct as tables plus blood. Research design utilized in this study is corelasional with statistical Chi Square test and Multiple Regression Analysis with 46 people function as sample. The sampling technique which is used non-probability sampling. Data collection is done by questionnaire and obsevation (check list). Result of this study shows that (1) there has been significant correlation between the understanding of pregnancy suggestion and the obedience of consuming increment tablet with significant level P = 0,038 < 0,05, (2) there has also been crucial correlation the obedeance of antenatal visit and the obedience of consuming increment tablet with significant level P = 0,00 < 0,05 and (3) there has been inportant correlation among the understanding of pregnancy suggestion the obedeance of antenatal visit and obedience of consuming increment tablet with significancy level 0,000 < 0,05 with consequently H0 is rejected and H1 is accepted.Herefore, it needs to be improved abaut the use of the MCH handbook and the role of health workers in increasing adherence to antenatal visits so that compliance with the consumpsion of blood tablet supplements for pregnant woment can increase